Inhibitory effect of yellow cempaka leaf (Michelia champaca Linn.) against Staphylococcus aureus and Escherichia coli - Fauzul Husna; Teuku Heriansyah; Shabrina Masturah (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2026)
Several studies have been conducted to develop herbal plants as alternatives to address infections. Yellow cempaka (Michelia champaca Linn.) is a natural ingredient that can serve as an alternative treatment. This study used a posttest-only control group to examine the antibacterial activity of the disc diffusion method against Staphylococcus aureus and Escherichia coli. This study included four treatment groups (10, 20, 40, and 80% ethanol extracts) and two control groups (10 μg amoxicillin for S. aureus, 5 μg ciprofloxacin for E. coli, and 96% ethanol as a negative control). The results showed that the ethanol extract of M. champaca leaves exhibited antibacterial activity against S. aureus at all concentrations tested, with mean inhibition zone diameters ranging from 13.70 mm to 23.11 mm. Statistical analysis showed that the 20% extract concentration had antibacterialactivity comparable to the positive control (p > 0.05), whereas the 40% and 80% concentrations showed significantly different inhibition zone diameters from the positive control (p < 0.05). In contrast, the ethanol extract of M. champaca leaves showed weak antibacterial activity against E. coli at all concentrations tested, with mean inhibition zone diameters ranging from 6.38 mm to 7.63 mm, which were significantly different from the positive control (p<0.05). These findings revealed that the ethanol extract of M. champaca leaves has potential as an alternative treatment for S. aureus infections. However, further research is needed to isolateand identify specific active compounds and to evaluate their efficacy and safety.